2005
DOI: 10.1124/jpet.105.091678
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine- and Amphetamine-Regulated Transcript (CART) Peptides Modulate the Locomotor and Motivational Properties of Psychostimulants

Abstract: Drug addiction results from a subversion of neural circuits that control motivation. Although the hedonic and addictive properties of psychostimulants and drugs of abuse are predominantly attributed to dopamine and glutamate, it is appreciated that other signaling molecules in the brain are important. This study suggests that cocaine-and amphetamine-regulated transcript (CART) peptides modulate the locomotor and motivational properties of psychostimulants. The behavioral effects of cocaine and amphetamine were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…Couceyro et al (2005) found a decrease in cocaine self-administration as well as altered amphetamine-induced locomotor activation and sensitization in CART knockout mice [ 8 ]. In contrast, another study found no differences in cocaine self-administration or cocaine-induced locomotor sensitization between wild type and CART knockout mice [ 33 ].…”
Section: Discussionmentioning
confidence: 96%
“…Couceyro et al (2005) found a decrease in cocaine self-administration as well as altered amphetamine-induced locomotor activation and sensitization in CART knockout mice [ 8 ]. In contrast, another study found no differences in cocaine self-administration or cocaine-induced locomotor sensitization between wild type and CART knockout mice [ 33 ].…”
Section: Discussionmentioning
confidence: 96%
“…ICV and intraaccumbal CART administration modulates mesolimbic dopaminergic (DA) activity (Yang et al, 2004;Shieh, 2003;Kuhar et al, 2005) and DA-mediated behaviors. For example, intraventral tegmental area (VTA) CART injections induce locomotor activation (which is blocked by DA antagonists), attenuates cocaine-induced spontaneous locomotion, and promotes conditioned placed preference (Jaworski et al, 2003;Couceyro et al, 2005;Kimmel et al, 2000). In addition, CART peptides have been shown to be potent anorectic and anxiogenic agents.…”
Section: Introductionmentioning
confidence: 99%
“…In studies in CART knockout mice, repeated doses of amphetamine produce a much smaller and delayed locomotor sensitization than in controls [38]. This is in direct contrast to a separate study, using different CART knockout mice, that found no change in the sensitization to cocaine in CART knockouts [39].…”
Section: Cart and Sensitization To Psychomotor Stimulantsmentioning
confidence: 57%
“…CART knockout mice also did not show any sensitization to the effects of amphetamine. The same mice, however showed no inhibition of open field activity and sucrose preference, indicating that the elimination of the CART gene did not effect locomotor ability or taste preference [38]. In contrast, separate studies using the different strain of CART knockout mice did not detect a difference in cocaine-induced locomotor activity, cocaine self-administration or sensitization to the behavioral effects of cocaine [39,42].…”
Section: Studies Using Cart Knockout Micementioning
confidence: 86%
See 1 more Smart Citation